A clinicopathological study of the oral lesions of Cowden disease. (27th November 2016) - Hammerschmidt, Mariana; Lourenço, Silvia Vanessa; Nico, Marcello Menta Simonsen
Abstract : Background: Cowden disease is a multisystemic cancer predisposition disorder, inherited in an autosomal dominant pattern. Cutaneous and visceral lesions are either malignant tumours or are believed to represent hamartomatous growths. Mucocutaneous lesions are present on almost 100% of affected individuals. Nonetheless, some authors consider that the mucocutaneous manifestations of Cowden disease are, in reality, viral warts at distinct steps of evolution. There are only a few studies regarding the oral manifestations of Cowden disease. Objectives: To study the oral manifestations of Cowden disease in nine patients clinically and histopathologically. Methods: The oral mucosal aspects of nine patients with clinical diagnosis of Cowden disease were photographed, and biopsies were taken from typical lesions. Results: All biopsied lesions depicted histopathological aspects suggestive of viral warts at distinct steps of development: incipient, well established and in regression. Conclusion: Our findings seem to reinforce the poorly understood hypothesis that the mucocutaneous manifestations of Cowden disease are in reality viral warts. Additional studies are needed to explain why a syndrome caused by the mutation of a tumour suppression gene may cause propensity to warts.